Strengthening Governance of Merah Putih Village/Urban Cooperatives (KDKMP) through Structured Lecturing and Basic Institutional Training - Sebayang, Saimara A M; Maisyarah, Renny; Faried, Annisa Ilmi; Lubis, Aditya Nugraha (CV Raskha Media Group, 2025)
This community service program aims to strengthen the governance of the Merah Putih Village/Urban Cooperatives (KDKMP) through structured lecturing and basic institutional training. The initiative responds to common challenges faced by Indonesian cooperatives, including weak managerial capacity, insufficient understanding of institutional roles, and low internal oversight. Conducted via Zoom in September 2025 and involving 182 participants across North Sumatra, the program utilized structured lecturing, interactive discussions, and simple simulations to convey cooperative governance principles. The results reveal significant improvement in participants’ comprehension of cooperative principles, institutional roles, accountability, and transparency. Furthermore, the program successfully facilitated the establishment of a communication network among KDKMP units, enabling the sharing of insights and best practices. This initiative aligns with the mandate of Presidential Instruction No. 9/2025 on the revitalization of KDKMP and reaffirms the strategic role of higher education institutions in enhancing cooperative governance through structured knowledge transfer.